2021
DOI: 10.1503/jpn.210049
|View full text |Cite
|
Sign up to set email alerts
|

BDNF levels in adolescent patients with anorexia nervosa increase continuously to supranormal levels 2.5 years after first hospitalization

Abstract: Background: Brain-derived neurotrophic factor (BDNF) influences brain plasticity and feeding behaviour, and it has been linked to anorexia nervosa in numerous studies. Findings in mostly adult patients point to reduced serum BDNF levels in the acute stage of anorexia nervosa and rising levels with weight recovery. However, it is unclear whether this increase leads to normalization or supranormal levels, a difference that is potentially important for the etiology of anorexia nervosa and relapse. Methods: We mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Except for four studies [ 37 , 40 42 ], all the other included ones reported a negative association between the level of BDNF and the presence of any type of eating disorders, meaning the levels of BDNF was lower among ED individuals compared to healthy controls (Table 1 ). None of the four studies reported the opposite recruited sex-matched controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Except for four studies [ 37 , 40 42 ], all the other included ones reported a negative association between the level of BDNF and the presence of any type of eating disorders, meaning the levels of BDNF was lower among ED individuals compared to healthy controls (Table 1 ). None of the four studies reported the opposite recruited sex-matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…None of the four studies reported the opposite recruited sex-matched controls. In fact, except for Borsdorf et al [ 37 ] study, having age-matched controls, the other three studies did not provide information on the detailed characteristics of their control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, low BDNF circulating levels have also been reported in other chronic mental disorders, including obsessive-compulsive disorder, major depression, bipolar disorder, and schizophrenia (Bocchio-Chiavetto et al, 2010 ; Fontenelle et al, 2012 ; Brand et al, 2015 ; Fernandes et al, 2015 ), reasonably pointing to BDNF as a potential biomarker of increased vulnerability also in AN. Regarding the modulation of BDNF after weight recovery, different investigations found a normalization of serum BDNF in weight-recovered AN patients (Ehrlich et al, 2009 ; Zwipp et al, 2014 ; Tyszkiewicz-Nwafor et al, 2019 ) or a rise to supranormal levels that are significantly higher than those of healthy controls (Borsdorf et al, 2021 ). Even though the human condition is less clear, body weight recovery in ABA rats restored circulating BDNF levels, suggesting that, in rats, peripheral mechanisms mediating BDNF homeostasis are still able to recover.…”
Section: Discussionmentioning
confidence: 99%